2015
DOI: 10.1074/jbc.m115.650911
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIII Interacts with the Endocytic Receptor Low-density Lipoprotein Receptor-related Protein 1 via an Extended Surface Comprising “Hot-Spot” Lysine Residues

Abstract: Background: It is unclear how the LDL receptor family binds large protein ligands. Results: HDX and lysine scanning identified factor (F)VIII regions and specific lysine residues binding low-density lipoprotein receptor-related protein 1 (LRP1). Conclusion: FVIII-LRP1 interaction involves multiple "hot-spot" lysine residues in the A3C1 domains. Significance: Our study sheds light on interactions of complex ligands with the LDL receptor family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 53 publications
5
29
1
Order By: Relevance
“…Further studies are necessary to determine whether any of these lysine residues are indeed critical for intact fVIII binding to full-length LRP1. Although our ionic strength dependence data suggest the involvement of at least two lysine residues in the interaction, the study of van den Biggelaar et al (31) did not identify any single pair of lysine residues that ablated binding when mutated, and the study concluded that fVIII interacts with LRP1 via an extended surface. This apparent discrepancy can be explained by the possibility that several lysine residues may compensate for one another.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Further studies are necessary to determine whether any of these lysine residues are indeed critical for intact fVIII binding to full-length LRP1. Although our ionic strength dependence data suggest the involvement of at least two lysine residues in the interaction, the study of van den Biggelaar et al (31) did not identify any single pair of lysine residues that ablated binding when mutated, and the study concluded that fVIII interacts with LRP1 via an extended surface. This apparent discrepancy can be explained by the possibility that several lysine residues may compensate for one another.…”
Section: Discussioncontrasting
confidence: 82%
“…Binding to LRP1-Prior studies examined the binding of the fVIII light chain to cluster II of LRP1 and observed that chemical modification of lysine residues in the fVIII light chain abolished its binding to cluster II, suggesting that lysine residues are important for this binding interaction (31). To determine whether lysine residues are critical for the binding of the entire fVIII molecule to full-length LRP1, we performed a similar experiment by first coating B domain-deleted fVIII (BDD-fVIII) in microtiter wells.…”
Section: Chemical Modification Of Fviii Lysine Residues Abolishes Itsmentioning
confidence: 99%
See 1 more Smart Citation
“…For certain LRP1 ligands, such as fVIII, identification of lysine pairs that contribute to LRP1 binding might be beneficial, as fVIII is used as a clinical product to treat hemophilia, and delaying its LRP1-mediated hepatic clearance would likely generate a molecule with a longer circulating half-life. Using hydrogen deuterium exchange experiments along with mutational analysis and SPR binding analysis, van den Biggelaar et al (50) concluded that the interaction between fVIII and cluster II of LRP1 occurs over an extended surface composed of multiple lysine residues and that no individual lysine residues dominate the binding interaction. However, if fVIII follows the same trend as RAP D1D2 and RAP D3, then mutation of two or more critical lysine residues would be required to sufficiently reduce its affinity for LRP1.…”
Section: Discussionmentioning
confidence: 99%
“…High affinity binding seems to involve the interaction with two or more LBDs requiring at least two lysine residues located at an appropriated distance - 18-20 Å according to structural data – which allows the simultaneous binding of two consecutive LBDs [56]. Likewise, the relative contribution of a single lysine residue of a ligand protein to the interaction may be difficult to rationalize in terms of stereo-chemical properties and the overall binding affinity may be the result of the additive effect of various weak binding sites [61].…”
Section: Resultsmentioning
confidence: 99%